Higher urge severity score predicts resumption of overactive bladder (OAB) medication following discontinuation of mirabegron treatment in patients with OAB1. Issue 2 (18th December 2018) - Wang, Chung‐Cheng; Jiang, Yung‐Hong; Kuo, Hann‐Chorng
Abstract : Objectives: This study investigated factors predicting the resumption of mirabegron following its discontinuation with successful treatment of overactive bladder (OAB). Methods: In all, 374 OAB patients reporting an improvement in subjective symptoms after a minimum of 3 months treatment with mirabegron 25 mg, q.d., were screened. Those wanting to continue with the medication (n = 109) were excluded from the study. The remaining 265 patients discontinued mirabegron and their outcomes were evaluated at baseline (discontinuation) and 1, 3, 6, 9, and 12 months using the International Prostate Symptom Score (IPSS), Overactive Bladder Symptom Score (OABSS), Urgency Severity Scale (USS), Patient's Perception of Bladder Condition (PPBC), and Global Response Assessment (GRA), as well as uroflowmetry and post‐void residual (PVR). Results: After mirabegron discontinuation, 203 patients completed follow‐up. The mean (±SD) duration from discontinuing medication to resumption of mirabegron was 2.25 ± 1.17 months (range 1–12 months). Compared with the 111 (54.7%) patients who did not resume mirabegron, the 92 (45.3%) patients who resumed mirabegron had a higher USS at time of discontinuation (1.18 ± 1.76 vs. 0.65 ± 1.33; P = 0.017). The USS was a strong predictor of mirabegron resumption ( P = 0.02; odds ratio 1.315; 95% confidence interval 1.051–1.646). Conclusions: Among OAB patients who were successfully treated with mirabegron for ≥3 months, nearly half requested resumption of mirabegron after discontinuation. A higher USS was found to predict retreatment after discontinuation of mirabegron in OAB patients.